THE CONTENT CHARACTERISTIC OF THE DIDACTIC CONDITIONS FOR THE FORMATION OF COGNITIVE UNIVERSAL EDUCATIONAL ACTIVITIES FOR THE FORMULATION AND SOLUTION OF THE PROBLEM AND THE WAYS OF THEIR IMPLEMENTATION IN THE EDUCATIONAL ACTIVITY OF THE PRIMARY SCHOOL - Alekseeva, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the article the actual problem of increasing the efficiency of the process of formation in cognitive universal educational actions of setting and solving the problem in junior schoolchildren is considered. The article contains the described and described didactic conditions for the formation of cognitive universal educational activities for the formulation and solution of the problem in younger schoolchildren. The pedagogical experience of the implementation of each didactic condition is represented through the constructed and tested teaching problem tasks. The carried out research, the analysis of its results made it possible to obtain data on the significance of the implementation of the didactic conditions for the formation of cognitive universal educational activities for the formulation and solution of the problem in younger schoolchildren in the educational activity of the primary school.